UV-Shielding and Photocatalytic Properties of ZnO-CeO2-TiO2 Composite - Li, Xiuping; Zhao, Rongxiang; Zhai, Yuchun; Ma, Peihua (Asian Journal of Chemistry, 2014)
The ZnO-CeO2-TiO2 composite oxide was rapidly synthesized by the combustion method using ascorbic acid as a new combustion agent. The composites were characterized by XRD, FT-IR, UV-visible and SEM. The experiments investigated the effect of molar ratio of burning agent, zinc, titanium and cerium ions on ZnO-CeO2-TiO2 (ZCT) composite. The ZnO-CeO2-TiO2 composite oxide with various morphologies, ultraviolet absorbing, photocatalytic and decolouring properties were obtained by changing molar ratio of burning agent, zinc, titanium and cerium ions. The composite oxide exhibited better properties of ultraviolet absorption, Light-stability of modified ZCT/paraffin wax and decolouration. Its ultraviolet properties are completely different from any monomer oxide. The composite oxide has better photocatalytic properties when molar ratio of burning agent, zinc, titanium and cerium ions is 8:4:0.25:1. Inorganic UV-shielding agent is firstly applied to improve light-stability of paraffin wax. The composite was modified in order to inorganic UV-shielding agent and paraffin wax can be mutually mixed.